Pattern of Handling Rejuvenation of Slum Areas in the Siantar Estate Huta Melati Nagori Siantar Estate Area, Siantar District, Simalungun Regency - Panatar Pakpahan; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to examine the Pattern of Handling Rejuvenation of Slum Areas in the Siantar Estate Huta MelatiNagori Siantar Estate Area, Siantar District, Simalungun Regency. This study uses a qualitative descriptivemethod that emphasizes the aspect of the natural condition of the object (as opposed to an experiment). Datacollection techniques are the means used to obtain the data and information needed to achieve researchobjectives. Data analysis is a process or effort to process data obtained from the results of interviews, field notesand documentation, into new information so that the characteristics of the data are good. The results of theresearch on the Existing Condition of the Siantar Estate Huta Melati Area is one of the settlements that show thecharacteristics of slums. The main problems in this area include poor infrastructure (damaged roads anddrainage), uninhabitable buildings, minimal sanitation systems, and limited access to clean water and electricity.In addition, socio-economic problems such as low income and education levels also aggravate environmentalconditions. Factors Causing the Emergence of Slums The emergence of slums in Siantar Estate Huta Melati iscaused by several factors, including uncontrolled population growth, land limitations, and irregular spatialplanning. The low level of community participation in environmental improvement programs and limited accessto basic facilities also contribute to the slum conditions in this area